Simultaneous Methemoglobinemia and Hemolytic Anemia Related to Trimethoprim-sulfamethoxazole and Phenazopyridine - Michael Reis; John Teijido (International Journal of Medical Toxicology and Forensic Medicine, 2024)
Background: Methemoglobinemia manifests with cyanosis but no respiratory distress. Many substances implicated in methemoglobinemia also are known to cause either drug-induced hemolysis or oxidative stress on erythrocytes, leading to hemolysis. This case report described a patient presenting acutely with both cyanosis and jaundice. Case Presentation The patient is a 76-year-old female with a history of chronic obstructive pulmonary disease and a recently diagnosed urinary tract infection (UTI) who presented to the emergency department with urinary frequency and dysuria. She had recently been started on trimethoprim-sulfamethoxazole (TMP-SMX) and phenazopyridine for her UTI. On physical exam, she had both cyanosis and jaundice, giving her skin a dull, gray color. She had hypoxia to 75% oxygen saturation, which did not remarkably respond to supplemental oxygen. She also had hyperbilirubinemia and anemia. Laboratory errors confounded the evaluation; however, there was high concern for methemoglobinemia, and empiric treatment was initiated. Methemoglobinemia was later confirmed and the patient improved, although she required multiple blood transfusions. After removing the offending agents, treating the methemoglobinemia, and providing supportive care for her hemolytic anemia, she improved and was discharged home. Conclusion: Although methemoglobinemia has a classic presentation of cyanosis without respiratory distress, additional coincident pathologies can easily confuse the clinical picture. Understanding the pathophysiology of methemoglobinemia is key to understanding why our patient also developed hemolysis. When cyanosis and jaundice are both present, simultaneous management of methemoglobinemia and hemolytic anemia may be needed. Special attention to glucose 6-phosphate dehydrogenase status is required in these circumstances to avoid patient harm with methylene blue.